Modelagem da dinâmica interativa rio-aquífero para região semiárida de dados escassos - Alencar, Júnio Moreira de (2019)
Models of river-aquifer interaction have been emerged as an important tool for effective management of water resources. Developing these models in semiarid regions is a great challenge and one of the main issues is the scarcity of hydrological data. Herein a model is proposed for simulation of river water and groundwater exchange for data-scarce regions. This model has been applied to the Experimental site (1014 km²) located in the Brazilian northeastern semi-arid region and based on three hydrological processes: (i) streamflow in natural rivers, which is modeled using the kinematic wave method, (ii) infiltration into heterogeneous soils, which is modeled using the Green-Ampt approach and (iii) groundwater flow, which is modeled using the two-dimensional partial differential equation for groundwater flow. The developed model simulates the river hydrograph accounting river water and groundwater exchange for each event. Initially, a sensitivity analysis was carried out and then the calibration procedure is evaluated using Coefficient of Nash and Sutcliffe (NS) for variation in the discharge hydrographs and the Mean Absolute Error (MAE) between simulated and observed groundwater heads. The results showed a calibration NS of 0.6 and EMA of 0.2 m. In the validation of the model, three events were used, two of short duration and small magnitude characterized by being of negative volumetric variation and the other of long duration and large magnitude characterized by being of positive volumetric variation. For model performance evaluation, NS and MAE are calculated. In addition, it was estimated the relative error (RE) in hydrograph volume and peak in relation to the observed data. Validation results showed a maximum MAE of 0.4 m, mean NS of 0.5, mean RE in hydrograph volume and peak, respectively, of 0.23 and 0.3. Considering the complexity of the proposed modeling and the uncertainties arising from the scarcity of data, the present model has been shown potential to simulate river-aquifer water exchanges for scarce data regions, but is not yet ready for real applications and needs to be evaluated in other semi-arid regions of distinct scale and lithology for a better understanding of their limitations. and potentialities and improvement of its internal routines.